Tumor-targeted PROTAC prodrug nanoplatform enables precise protein degradation and combination cancer therapy - Zou Zhi-feng; Yang Lei; Nie Hui-jun; Gao Jing; Lei Shu-min; Lai Yi; Zhang Fan; Wagner Ernst; Yu Hai-jun; Chen Xiao-hua; Xu Zhi-ai (Acta Pharmacologica Sinica, 2024)
Proteolysis targeting chimeras (PROTACs) have emerged as revolutionary anticancer therapeutics that degrade disease-causing proteins. However, the anticancer performance of PROTACs is often impaired by their insufficient bioavailability, unsatisfactory tumor specificity and ability to induce acquired drug resistance. Herein, we propose a polymer-conjugated PROTAC prodrug platform for the tumor-targeted delivery of the most prevalent von Hippel–Lindau (VHL)- and cereblon (CRBN)-based PROTACs, as well as for the precise codelivery of a degrader and conventional small-molecule drugs. The self-assembling PROTAC prodrug nanoparticles (NPs) can specifically target and be activated inside tumor cells to release the free PROTAC for precise protein degradation. The PROTAC prodrug NPs caused more efficient regression of MDA-MB-231 breast tumors in a mouse model by degrading bromodomain-containing protein 4 (BRD4) or cyclin-dependent kinase 9 (CDK9) with decreased systemic toxicity. In addition, we demonstrated that the PROTAC prodrug NPs can serve as a versatile platform for the codelivery of a PROTAC and chemotherapeutics for enhanced anticancer efficiency and combination benefits. This study paves the way for utilizing tumor-targeted protein degradation for precise anticancer therapy and the effective combination treatment of complex diseases.